Catheter-Associated Symptomatic Urinary Tract Infections in Nursing Homes—National Healthcare Safety Network, 2013–2018. (October 2020) - Mungai, Elisabeth; Edwards, Jonathan; Eure, Taniece; Anttila, Angela; Rowe, Theresa; Stone, Nimalie; Bell, Jeneita
Abstract : Background: Catheter-associated symptomatic urinary tract infections (CA-SUTIs) are a common adverse healthcare event in nursing homes and have been the focus of multiple prevention strategies. 1 In 2012, the CDC launched the NHSN Long-Term Care Facility (LTCF) Component, which nursing homes, the CDC, and prevention collaborators can use to monitor nursing home CA-SUTI incidence and prevention progress. 2 The objective of this analysis was to compare CA-SUTI rates and reporting patterns of nursing homes between 2013–2015 and 2016–2018. Methods: We analyzed CA-SUTI data from nursing homes reporting to the NHSN during 2013–2018. Consistent reporters submitted ≥6 months of complete data in any calendar year during the period. To potentially confirm patterns in CA-SUTI rates, we defined "consecutive" reporters, as nursing homes that submitted data for ≥6 months each year during 2013–2018. CA-SUTI incidence rates were calculated as the number of CA-SUTI events divided by the number of catheter days multiplied by 1, 000. Likelihood ratio tests using negative binomial regression were used to compare CA-SUTI rates from 2016–2018 and 2013–2015 among both consistent and consecutive reporters. Results: During 2013–2018, the number of nursing homes submitting at least 1 month of CA-SUTI data to NHSN increased from 60 to 120 (Fig. 1). Among these nursing homes, 194 (88%) were consistent reporters. The pooled CA-SUTI rate of 1.77 per 1, 000 catheter days in 2016–2018 was significantly lower than the pooled CA-SUTI rate of 2.45 per 1, 000 catheter days in 2013–2015 among consistent reporters by 24% (Table 1). Also, 50 consecutive reporters submitted CA-SUTI data during 2013–2018. Among these consecutive reporters, the pooled CA-SUTI rate of 2.11 per 1, 000 catheter days in 2016–2018 was significantly lower than the rate of 2.53 per 1, 000 catheter days in 2013–2015 by 21% (Table 1). Conclusions: This analysis suggests that nursing homes using NHSN for CA-SUTI surveillance have made progress in prevention efforts. During 2013–2018, evidence showed that CA-SUTI incidence rates declined among consistent reporters between the 2 reporting periods. This decrease was verified among consecutive reporters. Additional study is needed to determine which factors account for varying reporting patterns and differential CA-SUTI incidence. Funding: None Disclosures: None